Increased ventilation heterogeneity in asthma can be attributed to proximal bronchioles. Issue 3 (12th March 2020) - Foy, Brody; Kay, David; Siddiqui, Salman; Brightling, Chris; Paiva, Manuel; Verbanck, Sylvia
In recent years, tests of ventilation heterogeneity such as the multiple breath washout (MBW) have gained popularity as potentially sensitive measures of disease in the small airways [1]. The premise of a non-invasive test, such as the MBW, is that morphological alterations at differing lung depths can be sampled at the mouth via their effect on ventilation heterogeneity. MBW phase III slope derived indices of ventilation heterogeneity include the conductive slope index (Scond), a purely convection-dependent contribution generated in the conducting zone of the lungs, and the acinar slope index (Sacin), brought about by diffusion–convection mechanisms operating near acinar entrances in the respiratory zone [2, 3]. By combining patient-specific CT-based airways with a clinically validated lung model, the proximal bronchioles were identified as the airways where structural abnormality can explain the increased convective ventilation heterogeneity in asthma patients http://bit.ly/2COT0Qh